Circular RNA circBFAR promotes the progression of pancreatic ductal adenocarcinoma via the miR-34b-5p/MET/Akt axis - Guo, Xiaofeng (Mol Cancer, 2020)
BACKGROUND: Accumulating evidence suggests that circular RNAs (circRNAs) are important participants in cancer progression. However, the biological processes and underlying mechanisms of circRNAs in pancreatic ductal adenocarcinoma (PDAC) are unclear. METHOD: CircRNAs were verified by Sanger sequencing. Colony formation, 5-Ethynyl-2′-deoxyuridine (EdU), and Transwell assays were performed to investigate the effect of circBFAR on the proliferation, invasion, and migration of PDAC cells in vitro. RNA pull-down assays were conducted to verify the binding of circBFAR with microRNA miR-34b-5p. RESULTS: In the present study, we identified a novel circRNA (termed as circBFAR, hsa_circ_0009065) that was upregulated in a 208-case cohort of patients with PDAC. The ectopic expression of circBFAR correlated positively with the tumor-node-metastasis (TNM) stage and was related to poorer prognosis of patients with PDAC. Moreover, circBFAR knockdown dramatically inhibited the proliferation and motility of PDAC cells in vitro and their tumor-promoting and metastasis properties in in vivo models. Mechanistically, circBFAR upregulated mesenchymal-epithelial transition factor (MET) expression via sponging miR-34b-5p. Additionally, circBFAR overexpression increased the expression of MET and activated downstream phosphorylation of Akt (Ser 473) and further activated the MET/PI3K/Akt signaling pathway, which ultimately promoted the progression of PDAC cells. Importantly, application of MET inhibitors could significantly attenuate circBFAR-mediated tumorigenesis in vivo. CONCLUSIONS: Our findings showed that circBFAR plays an important role in the proliferation and metastasis of PDAC, which might be explored as a potential prognostic marker and therapeutic target for PDAC.